The Role of Authentic Leadership in Improving Teacher Work Discipline at Yasiska Vocational School - Firda Zahraningtyas; Hasyim Asy’ari; Jejen Musfah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The purpose of this study is to explain the concept of authentic leadership. Authentic leadership includes something that has growing rapidly in the last two decades, and it is interesting to discuss. Authentic leadership as a pattern of leader behavior that utilize and enhances positive psychological capacity and a positive ethical climate, to foster greater self-awareness, internalized moral perspective, balanced information processing, and relational transparency from leaders who work with followers, encourage positive self-development. In its implementation authentic leadership is a leader who is able to be honest with himself and followers. Authentic leaders must be aware of themselves and be able to foster self-awareness of their employees to work optimally in the organization.